Unreal engine physics essentials : gain practical knowledge of mathematical and physics concepts in order to design and develop an awesome game world using Unreal Engine 4 /: gain practical knowledge of mathematical and physics concepts in order to design and develop an awesome game world using Unreal Engine 4. ([2015]) - Emperore, Katax; Sherry, Devin
No abstract available